2008
DOI: 10.7547/0980469
|View full text |Cite
|
Sign up to set email alerts
|

Acute Traumatic Open Posterolateral Dislocation of the Ankle Without Tearing of the Tibiofibular Syndesmosis Ligaments

Abstract: Pure open dislocation of the ankle, or dislocation not accompanied by rupture of the tibiofibular syndesmosis ligaments or fractures of the malleoli or of the posterior border of the tibia, is an extremely rare injury. A 62-year-old man injured his right ankle in a motor vehicle accident. Besides posterolateral ankle dislocation, there was a 7-cm transverse skin cut on the medial malleolus, and the distal end of the tibia was exposed. After reduction, we made a 2- to 2.5-cm longitudinal incision on the lateral… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
4
0
2

Year Published

2009
2009
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 17 publications
1
4
0
2
Order By: Relevance
“…Ankle fractures and fracture dislocations are common injuries in orthopaedic practice however pure ankle dislocation without an associated fracture is extremely rare [3,5,19]. The rarity is described to be due to mechanical efficacy of the ankle mortise and resistance of the ankle ligaments being greater than bone making fracture common [6].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Ankle fractures and fracture dislocations are common injuries in orthopaedic practice however pure ankle dislocation without an associated fracture is extremely rare [3,5,19]. The rarity is described to be due to mechanical efficacy of the ankle mortise and resistance of the ankle ligaments being greater than bone making fracture common [6].…”
Section: Discussionmentioning
confidence: 99%
“…Our patient had neither history of previous ankle sprain nor an evidence of ligamentous laxity or a muscle weakness in the physical examination. ‘For evaluating the medial malleolus hypoplasia, the ratio between the length of the medial (B) and lateral (A) malleolus was evaluated by the method of Elisé et al [20] in anteroposterior ankle radiograph and it was found to be in normal ranges (eg:0.62) (Figure 6). ’…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The disruption of deltoid ligament producing a marked decrease in the tibiotalar contact area, thus the severity of a medial injury will determine the reduction of ankle stability [32]. Kaneko et al [29] and Demiralp et al [33] reported that they performed medial capsule and deltoid ligament restoration in posterolateral cases and gained satisfactory follow-up outcome.…”
Section: The Deltoid Ligamentsmentioning
confidence: 99%
“…Es sind neurovaskuläre Folgeschäden, persistierende Gelenkinstabilitäten, posttraumatische Arthrosen sowie heterotope Ossifikationen der Gelenkkapsel, vor allem nach offenen Verletzungen, beschrieben [2, 5 -7]. Im Folgenden kommt es gehäuft zu einer funktionell irrelevanten Bewegungseinschränkung des OSGs zwischen 0 und 10°für Plantarflexion, In-und Eversion wie auch Dorsalextension [8,9]. Dabei ist das funktionelle Ergebnis bei offenen Luxationen schlechter und die Komplikationsrate höher [6].…”
Section: Diskussionunclassified